2006
DOI: 10.1016/j.ejcts.2006.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Does retrograde cerebral perfusion via superior vena cava cannulation protect the brain?

Abstract: As a rule, anatomically and functionally competent valves in the proximal IJV are present. In human beings, they obstruct the direct retrograde inlet to the intracranial venous system, which suggests an unbalanced and unreliable perfusion of the brain. Therefore, retrograde cerebral perfusion by cannulating the superior vena cava may help flushing out embolism and supporting 'the cold jacket' of the brain. However, its effect of retrograde backflow cannot be a sign of adequate cerebral perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…This re ects the fact that the RIVP + ACP group had a slightly lower RIFLE classi cation, although aortic dissection in that group more often involved the celiac trunk artery and right renal artery than in the ACP group. The protective effects may be explained by RIVP blood for providing continuous oxygenation to the lower body, as well as cooling and ushing out the particular embolic debris, similarly to retrograde superior vena caval perfusion 25 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This re ects the fact that the RIVP + ACP group had a slightly lower RIFLE classi cation, although aortic dissection in that group more often involved the celiac trunk artery and right renal artery than in the ACP group. The protective effects may be explained by RIVP blood for providing continuous oxygenation to the lower body, as well as cooling and ushing out the particular embolic debris, similarly to retrograde superior vena caval perfusion 25 .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, patients in the ACP group were maintained at a nasopharyngeal temperature of 24-26 °C and a rectal temperature of 26-28 °C in accordance with previous reports. 26,27 The higher temperature in the RIVP + ACP group shortened CPB time, which may be bene t to shorten the ventilation time via attenuating the in ammatory response in the lung induced by the arti cial material of the CPB circuit 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Cheung and associates measured O 2 extraction, pH, and PCO 2 from the RCP inflow and outflow in humans which demonstrated near maximal brain oxygen extraction suggesting relative cerebral hypoperfusion during RCP (14). A cadaveric study using in vitro venous retroperfusion showed that in humans most of the valves of the internal jugular vein are competent and potentially obstruct RCP (15). Transcranial Doppler studies aimed at evaluating the flow velocity in the middle cerebral artery during RCP gave mixed results (16).…”
Section: Discussionmentioning
confidence: 99%
“…Competent valves in the internal jugular venous system can impede retrograde flow, although blood flow may still reach the brain through collateral veins [83]. McQuillen et al performed MRI studies on newborns with CHD.…”
Section: Decreasing Neurologic Morbidity During Cpbmentioning
confidence: 99%